Расчет параметров рабочего процесса виброабразивной обработки деталей на вибрирующем держателе в неподвижном контейнере - Бранспиз, Елена Владимировна; Калмыков, Михаил Александрович; Нечай, Елена Владимировна (Eastern-European Journal of Enterprise Technologies, 2009)
Basic parameters, influencing on the process of finish vibroabrasive treatment of details on a vibrating holder in an immobile container, filled with an abrasive medium, being in thefree state, are determined and the experimental results of resistance coefficient of abrasive medium are resulted, that allows to pass for necessary tool drive power determination.